Mathematics for elementary teachers : a contemporary approach - Musser, Gary L.; Burger, William F.; Peterson, Blake E. (River Street : Hoboken : John Wiley and sons, 2003)
This title contains the mathematics teachers need for teaching at the elementary and middle school levels. Coverage in the book moves from the concrete to the pictorial to the abstract, reflecting the way math is generally taught in elementary classrooms.
Includes bibliographical references and index.
Keywords: Mathematics -- Study and teaching (Elementary).